The Contribution of Teachers’ Beliefs to Pedagogical Grammar Instruction in English as Second and Foreign Language - Erna Nawir (UICELL, 2020)
Having background knowledge and past experiences of teaching, a teacher has been equipped with one of the sufficient and essential tools to ensure that his teaching process will be run as he plans. It is generally known as belief. Teaching English to learners as second or and foreign language means teaching the two most important aspects of the language that is vocabularies and grammar. This article deals with one of the aspects in teaching and learning English that is grammar which is of utmost significance in any languages. Teaching grammar means involving pedagogical theories to figure out the most adjustable teaching method to get the learners not only to view the syntactic structures of the target language but also to be aware of its importance and the way to learn it which later on is known as pedagogical grammar. The paper highlights teachers’ beliefs that influence their way of teaching in grammar reflected in their grammar instruction. Teaching experiences and some principles are put into a consideration to construct the beliefs contributing to teachers’ knowledge of pedagogical grammar instruction. Nevertheless, a teaching approach (Communicative Language Teaching/CLT) is required to be employed in order to ensure that the learners will be able to optimize their language competence by learning the grammar. Therefore, there is a big possibility ahead that teachers will be able to improve their own pedagogical grammar instruction by utilizing their teaching beliefs in their learners’ language acquisition process in teaching English as second and or foreign language.